ONTOLOGI RIBA DALAM HADIS (Kajian Tematik Hadis Ahkam) - Edy Saputra (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2021)
This article contains a thematic study of Ahkam's hadith on the ontology of riba. This study is included in the library research category. The study method used is descriptive analytical. Primary data in this study came from nine primary hadith books, namely Al-Kutub Al-Tis'ah consisting of Sahih Al-Bukhari, Sahih Muslim, Sunan Abu Daud, Sunan Al-Tirmizi, Sunan Al-Nasa'I, Sunan Ibn Majah. , Muwatha 'Malik, Sunan Al-Darimi, and Musnad Ahmad. As for data collection techniques, the author uses the android application